Symbols, Enigmas, Political Allusions and the Legend of Socrates in Dio Chrysostom’s Olympic Discourse - Ranko Kozić (Athens Journal of Humanities & Arts)
Close analysis of the Olympic Discourse showed a wealth of detail, thanks to which we were able to see the poetics of the great orator of Prusa in a new light and in all its aspects, with those political and strategic, otherwise overlooked in previous research on the subject, gaining in importance, in so far as it turned out that Dio felt a deep aversion to Roman rule and hence aspired to a noble mission to join in the project of putting into practice the key ideas of Socrates’ political testament in the Alcibiades, thus following the example seta long time before by both Xenophon and Isocrates, the testament’s first executors. Close analysis has also shown that the literary aspect of Dio’s poetics is, too, essentially based on the legend of Socrates, as evidenced by the fact that the entire discourse might be characterized as a detailed elaboration of the theses on art, succinctly outlined in Socrates’ conversations with the major exponents of painting and sculpture of his own time in Xenophon’s Memorabilia. The fact that both the beginning and the end of the Olympic Discourse are marked by meaning- and symbol-laden admonitions, standing in sharp contrast to a serene and solemn atmosphere of the festival and moreover closely associated with the mentioned testament, clearly speaks of Dio’s impressive sense of composition. Method used in this study is essentially based on combining together evidence provided in both Dio’s three largely disparate writings (two short essays on Socrates and Homer and the Olympic discourse) and Isocrates’ Panathenaicus with the aim of decoding the author’s poetics and, by the same token, the true nature of the Second Sophistic.